PENGARUH PENDIDIKAN KESEHATAN REPRODUKSI PADA PEER GROUP (TEMAN SEBAYA) TERHADAP PENGETAHUAN DAN PERSEPSI REMAJA TENTANG PENDEWASAAN USIA PERKAWINAN DI SMA NEGERI 1 KECAMATAN NAMORAMBE KAB. DELI SERDANG 2018 - Irma linda (COLOSTRUM : Jurnal Kebidanan, 2020)
Background: Early marriages are at high risk of marital failure, poor family quality, young pregnancies at risk of maternal death, and the risk of being mentally ill to foster marriage and be responsible parents. Objective: To determine the effect of reproductive health education on peer groups (peers) on the knowledge and perceptions of adolescents about marriage age maturity. Method: This research uses the Quasi experimental method with One group pre and post test design, conducted from May to September 2018. The statistical analysis used in this study is a paired T test with a confidence level of 95% (? = 0, 05). Results: There is an average difference in the mean value of adolescent knowledge between the first and second measurements is 0.50 with a standard deviation of 1.922. The mean difference in mean scores of adolescent perceptions between the first and second measurements was 4.42 with a standard deviation of 9.611. Conclusion: There is a significant difference between adolescent knowledge on the pretest and posttest measurements with a value of P = 0.002, and there is a significant difference between adolescent perceptions on the pretest and posttest measurements with a value of p = 0.001. Increasing the number of facilities and facilities related to reproductive health education by peer groups (peers) in adolescents is carried out on an ongoing basis at school, in collaboration with local health workers as prevention of risky pregnancy.